Evaluating the safety of intermittent intravenous sildenafil in infants with pulmonary hypertension. Issue 2 (24th June 2016) - Darland, Leanna K.; Dinh, Kimberly L.; Kim, Shelly; Placencia, Jennifer L.; Varghese, Nidhy P.; Ruiz, Fadel; Mallory, George B.; Fernandes, Caraciolo J.
Summary: Objective: To compare the occurrence of hypotension following administration of intermittent intravenous (IV) and enteral sildenafil for treatment of pulmonary hypertension (PH) in infants. We hypothesized there may be more adverse effects associated with intermittent IV sildenafil compared with enteral sildenafil. Methods: This was a retrospective matched‐cohort study conducted in a tertiary care children's hospital. Patients were included if they were less than 1 year of age and received intermittent sildenafil for PH. Exclusion criteria consisted of concurrent extracorporeal membrane oxygenation during the initiation of sildenafil, the utilization of sildenafil as a one‐time dose, continuation of home‐dosing regimen, or inclusion in the other cohort. A total of 40 patients were matched 1:1 based on postmenstrual age and primary diagnosis. Results: There was no statistically significant difference in the primary outcome, as 30% (6/20) of patients receiving IV sildenafil required a hypotension intervention compared with 10% (2/20) in the enteral cohort ( P = 0.24). The majority of interventions occurred within 24 hr of the initiation of sildenafil with 4/6 patients (67%) in the IV group and 2/2 patients (100%) in the enteral group, respectively. Baseline mean arterial pressure was significantly lower in the IV patients that required an intervention compared with those that did not (44 ± 6.3 vs. 65 ± 13.4 mmHg, P = 0.0024). Conclusions: There were no statistically significant differences in safety outcomes between intermittent IV and enteral sildenafil in infants with PH. Hemodynamic parameters should be monitored closely upon sildenafil initiation. Limitations include the retrospective nature and small sample size.Pediatr Pulmonol. 2017;52:232–237. © 2016 Wiley Periodicals, Inc.